Potensi masjid sebagai produk pelancongan di Malaysia / Azarudin Awang ...[et al.] - Awang, Azarudin; Zakaria, Zainuddin; Abdul Ghafar, Mohd Sabri; Ismail, Noralisa; Jusoh, Zuraini (Universiti Teknologi MARA, Kedah, 2021)
The mosque is an Islamic Syiar that is visible, clear and easily recognizable. In the time of Rasullullah S.A.W and the time of the Khulafa', the mosque played a major role in religious activities, society, culture, politics, education, and even the spread of Islam. The role and function of the mosque is likened to the heart of the Muslim community. If the heart is no longer functioning, the body will surely die. Realizing the function and role of mosques that are important to the Muslim community, great mosques of the world are built in grand and beautiful fashion as a symbol of Islamic strength and civilization. Mosques are built at very strategic locations, especially in settlement areas or large cities of the world. Mosques that are built with great aesthetic and architectural value may create attention and attract not only Muslims, but also non-Muslims visitors. The beautiful architecture of mosque has become an attractive tourism product that may attracts local and foreign tourists which may improve a country's economy. This paper aims to measure and highlight the potential of mosques as one of the tourism products in Malaysia under the category of Islamic tourism. Data were obtained from previous studies that discuses on studies related to mosques as a tourism product in Malaysia. The results of the study revealed that mosques as part of a tourism products has the potential to contribute to the development of the tourism industry through homestay activities, pilgrimages and worship at mosques; and 'Mosque Tourism' program. This study is significant because Malaysia has become a global tourist destination that offers various categories of tourism products that caters to both local and foreign tourists.